Cyborgs vs. Vatniks: Hybridity, Weaponized Information, and Mediatized Reality in Recent Ukrainian War Films - Ladygina, Yuliya V. (East/West, 2022)
Focusing on Akhtem Seitablaiev’s blockbuster Kiborhy: Heroi ne vmyraiut' (Cyborgs: Heroes Never Die, 2017) and Sergei Loznitsa’s auteur production Donbass (2018), this article argues that the latest cycle of Ukrainian war films merits critical attention as an astute record of conspicuous social transformations in today’s Ukraine and as a medium that presents an original perspective on the hybrid nature of modern war and its mediatization, the latter being a relatively new theme in war films broadly defined. The article uses post-colonial and cyborg theories of hybridity, Baudrillard’s concept of simulacra, and the Marxist notion of “false consciousness” to illustrate how post-Soviet, post-colonial, and post-truth aspects of war-torn Ukraine conflate in Seitablaev’s and Loznitsa’s works to bring to the fore a recent shift in the nature of warfare itself. As the two films unequivocally demonstrate, the latter is defined not so much by high-tech armed operations and direct annihilation of the opponent as by contactless warfare, as well as its consequences for those directly influenced by it.